Effect of Muscle Relaxation Training on Perceived Stress and Rumination in Patients with Dental Anxiety - Saei Nia, Mina; Asgari, Parviz; Saraj Khorrami, Naser; Naderi, Farah; Safarzadeh, Sahar (Journal of Dental School, 2022)
Objectives The present study aimed to investigate the effect of muscle relaxation training on perceived stress and rumination in patients with dental anxiety. Methods This was a quasi-experimental study (pretest-posttest design and a control group). The statistical population comprised of all patients with dental anxiety who visited dental clinics in Ahvaz city (Iran) in 2019. The sample consisted of 30 patients with dental anxiety selected through convenience sampling. The participants were randomly divided into experimental and control groups (15 participants per group). The experimental group received six 90-minute sessions of muscle relaxation, while the control group received no intervention. The research instruments included the Perceived Stress Scale (PSS), the Ruminative Responses Scale (RRS), and the Modified Dental Anxiety Scale (MDAS). The data were analyzed by MANCOVA and ANCOVA. Results The mean ± standard deviation (SD) of the post-test scores of perceived stress and rumination in the experimental group were 21.53±5.60 and 29.06±6.70, respectively which were significantly different from the scores in the control group (54.33±3.71 and 70.86±7.55, respectively). The muscle relaxation training reduced the perceived stress and rumination in patients with dental anxiety in the experimental group compared with the control group (P<0.001). Conclusion Muscle relaxation training may thus be administered as an effective approach to mitigate perceived stress and rumination in patients with dental anxiety.